The THE EFFECT OF RANGE OF MOTION (ROM) EXERCISES ON INCREASING MUSCLE STRENGTH IN STROKE PATIENTS IN BOUGENVILLE ROOM RSUD SAYANG CIANJUR - Nunung Liawati, Nunung Liawati; Yusuf Arifin, Yusuf Arifin; Susilawati, Susilawati; Iin Patimah, Iin Patimah (Karsa Husada Health Institute Garut, 2025)
ABSTRACT Stroke is the second leading cause of death and the third leading cause of disability in the world. Stroke occurs when some brain cells die due to lack of oxygen due to obstruction of blood flow to the brain or rupture). The purpose of the study was to determine the effect of (ROM) on increasing muscle strength in stroke patients Muscle strength of the extremities is still a major problem faced by stroke patients who experience hemiparese, One of the therapies performed to restore muscle strength in stroke patients is Range Of Motion (ROM). This study used a quasy experimental design or type of research with a One Group Pretest-Posttest approach. The research sample was non-hemorrhagic stroke patients with hemiparese totaling 17 respondents selected by purvosive sampling and accidental sampling techniques. Research instruments: Muscle strength observation sheet (MMST), SOP Range Of Motion (ROM). Data were analyzed with univariate and bivariate. Based on the results of research conducted in the Bougenville Room, Sayang Cianjur Hospital, the results of the analysis with the Wilxocon test obtained a value of p = 0.001 with the accuracy of the value ? = 0.05 or p < 0.05 which means Ho is rejected and Ha is accepted. Range Of Motion (ROM) exercise has an effect on muscle strength in stroke patients in the Bougenville Room at Sayang Cianjur Hospital, so Range Of Motion (ROM) exercise can be used as a management and treatment to increase muscle strength in stroke patients.